"Here Is a Good Boke to Lerne": Practical Books, the Coming of the Press, and the Search for Knowledge, ca. 1400–1560. (9th May 2019) - Reynolds, Melissa
Abstract: This article compares the circulation and reception of useful knowledge—from medical and craft recipes to prognostications and agricultural treatises—in late medieval English manuscripts and early printed practical books. It first surveys the contents and composition of eighty-eight fifteenth-century vernacular practical manuscripts identified in significant collections in the United States and United Kingdom. Close analysis of four of these late medieval practical miscellanies reveals that their compilers saw these manuscripts as repositories for the collection of an established body of useful knowledge. The article then traces the transmission of these medieval practical texts in early printed books. As the pressures of a commercial book market gradually transformed how these practical texts were presented, readers became conditioned to discover "new" knowledge in the pages of printed books. The introduction to England of the "book of secrets" in 1558 encouraged readers to hunt for "secrets" in unpublished medieval manuscripts, ensuring that these century-old sources would remain important sites for useful knowledge well into the early modern era.